Hemorrhagic Microthrombovasculitis: Primary Hemostasis and Immunological Parameters - AR Raimzhanov; OA Dzhakypbaev (Клиническая онкогематология)
Background & Aims. Hemorrhagic microthrombovasculitis (HMTV) is the most common disease among hypersensitive immunocomplex systemic vasculites. The high prevalence of the disease and increasing growth of the number of HMTV patients, the severity of the clinical course, and frequent joint, GIT, and kidney involvement (30–50 %) demonstrate the important social and economic significance of this problem and the need in further specification and evaluation of unspecified pathogenetic factors with development of new treatment approaches. The aim of this work is to evaluate the ristomycin-induced platelet aggregation, cytokines and homocysteine levels in HMTV patients.